Hyperuricemia and chronic kidney disease - Olga Kompaniets (Ukrainian Journal of Nephrology and Dialysis, 2021)
The article is devoted to a review of the literature on the impact of hyperuricemia on the development and progression of chronic kidney disease (CKD). The tendency of changes of views on the role of uric acid in the pathogenesis of CKD is demonstrated. An analysis of experimental, epidemiological and clinical studies on the effects of uric acid on the physiology of the nephron and endothelial tissues, the relationship of hyperuricemia with metabolic and cardiorenal syndromes.